1999
DOI: 10.1074/jbc.274.15.10405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for GroEL/GroES-mediated Folding of a Large 86-kDa Fusion Polypeptide in Vitro

Abstract: Our understanding of mechanisms for GroEL/GroESassisted protein folding to date has been derived mostly from studies with small proteins. Little is known concerning the interaction of these chaperonins with large multidomain polypeptides during folding. In the present study, we investigated chaperonin-dependent folding of a large 86-kDa fusion polypeptide, in which the mature maltose-binding protein (MBP) sequence was linked to the N terminus of the ␣ subunit of the decarboxylase (E1) component of the human mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…It has been suggested that this movement results in doubling the volume of the cis ring cavity of GroEL to accommodate a polypeptide of larger than 70 kDa in size (7). In support of this suggestion, the 75-kDa methylmalonyl-CoA mutase (9), an 82-kDa fusion protein of three tandem green fluorescent proteins (10), and an 86-kDa fusion polypeptide (11) were shown to bind to GroEL, but cis capping of these proteins by GroES did not occur.…”
supporting
confidence: 51%
“…It has been suggested that this movement results in doubling the volume of the cis ring cavity of GroEL to accommodate a polypeptide of larger than 70 kDa in size (7). In support of this suggestion, the 75-kDa methylmalonyl-CoA mutase (9), an 82-kDa fusion protein of three tandem green fluorescent proteins (10), and an 86-kDa fusion polypeptide (11) were shown to bind to GroEL, but cis capping of these proteins by GroES did not occur.…”
supporting
confidence: 51%
“…In fact, Douette et al have presented evidence that MBP and NusA fusion proteins interact with GroEL in E. coli [21]. It is not entirely clear, however, how these rather large fusion proteins could engage the GroEL/GroES chaperone apparatus in the same manner as its natural substrates do, because the size of the chaperone cavity would seem to limit substrates to approximately 50 kDa [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported in vitro reconstitution of human BCKD with an absolute requirement for GroEL/GroES and Mg-ATP (30,31); however, the kinetics of BCKD reconstitution was markedly slower than that of chaperonin-mediated refolding of other proteins. A GroEL-␣␤ complex resulting from binding of a large 85-kDa ␣␤ heterodimeric intermediate to GroEL was also isolated.…”
mentioning
confidence: 99%